1993
DOI: 10.7863/jum.1993.12.9.545
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis of arteriovenous fistula and pseudoaneurysm after biopsy of a transplanted kidney

Abstract: Ultrasonography is useful in assessing the trans~ planted kidney for hydronephrosis and postoperative fluid collections. Percutaneous biopsy, however, re~ mains the definitive method of distinguishing between rejection and other causes of transplant failure. Unfortunately, biopsy procedures are not without complications, including bleeding, infection, and vascular problems such as A V fistula and pseudoaneurysms.t,2 CSDI provides a rapid, sensitive, and noninvasive technique for detecting vascular complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Most of the time, they are asymptomatic when small and spontaneously thrombose. 43 However, when they are symptomatic, a patient can present with a pulsatile mass in the pelvis, flank pain, renal dysfunction secondary to compression of artery branches or shunting of blood, or hemorrhage from rupture. Although these lesions can be managed surgically, RAE is preferred if they are amenable to embolization to minimize the loss of normal functioning renal parenchyma (Fig.…”
Section: Arteriovenous Fistulasmentioning
confidence: 99%
“…Most of the time, they are asymptomatic when small and spontaneously thrombose. 43 However, when they are symptomatic, a patient can present with a pulsatile mass in the pelvis, flank pain, renal dysfunction secondary to compression of artery branches or shunting of blood, or hemorrhage from rupture. Although these lesions can be managed surgically, RAE is preferred if they are amenable to embolization to minimize the loss of normal functioning renal parenchyma (Fig.…”
Section: Arteriovenous Fistulasmentioning
confidence: 99%
“…Subsequently in the course of repair processes of the perivascular tissues, they are liquefied and dissolved, leaving a sac continuous with the endluminal space (4). Biopsy‐induced AVFs and pseudoaneurysms are known to be accurately identified by echo‐Doppler imaging, which can detect intrarenal blood flow abnormalities (5, 6), and selective arteriography, which can evaluate size and localization (1, 7). Some authors have suggested conservative management of biopsy‐related renal allograft injury (7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy-induced AVF and pseudoaneurysm are known to be correctly identifi ed by CDU imaging, which can distinguish intrarenal blood fl ow abnormalities (36) and by selective arteriography, which can evaluate size and localization (37). Although angiography is known as a gold standard for the diagnosis of postbiopsy AVF and pseudoaneurysm, CDU has been used effectively to detect AVF and pseudoaneurysm after biopsy (26,31,32,(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%